Impact of Anxiety and Affect on Quality of Life among Youth - Ananya Rana; Smriti Sethi (International Journal of Education Sciences, 2026)
Youth well-being is an important phenomenon comprising physical, psychological, and social health, where the psychological factors such as anxiety and affect play an essential role in determining Quality of Life (QOL). Young people experience multiple transitions and they are at risk of anxiety disorders that in turn can have adverse effects on academic achievement, physical health, emotional well-being and relationships. Furthermore, affect has a role in the management of emotions and well-being. Positive affect leads to satisfaction, interest and happiness while negative affect is associatedwith sadness, gloom and maladjustment. Thus, the study aimed to investigate the impact of anxiety and affect on the life quality (QOL) among youth. Hypotheses were formed on the basis of objectives. Random sampling method was used to select 130 youth (65 males and 65 females), and standardized psychological instruments were used to collect data. Descriptive statistics (t-test), regression analysis and Pearson’s correlation were the statistical techniques utilized. Results revealed that substantialgender differences were present in anxiety and negative affect, with females scoring higher. Anxiety was negatively correlated with all QOL domains; and positive affect had a strong positive correlationwith all the dimensions of QOL in youth. Negative affect was seen to be negatively correlated with psychological and social QOL. Regression analysis established that anxiety and affect are important predictors of QOL. Positive affect significantly predicts life quality, explaining 24–39% variance in the different domains. These results showcased the importance of having support systems and mental health programs that seek to lessen anxiety, increase positive affect, and build emotional strength in youth. Significantly, through the improvement of these psychological factors, the life quality of youth can be enhanced, emphasizing the need for organized counseling services and support initiatives from families, peers, and society as a whole.
Keywords: Anxiety; Quality of life; negative affect; positive affect; well-being; youth